#### Answer

$y' = 3.2x^{2.2} $

#### Work Step by Step

$y = \sqrt[3] (x^{9.6}) + 2e^{1.3}$
$y = x^{3.2} +2e^{1.3}$
$y' = 3.2x^{2.2} + 0 $
$y' = 3.2x^{2.2} $

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$y' = 3.2x^{2.2} $

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.